The Implementation of Communicative Language Teaching (CLT) and Factors Hindering Teachers from Implementing it in High School - Chang, Afnesha Noveriana; Suparmi, Suparmi (Institut Agama Islam Negeri Kendari, 2020)
This study attempts to see the implementation of communicative language teaching and to investigate factors hindering high school teachers from implementing it. Data were collected using online questionnaire and interview. This questionnaire was administered to 29 senior high school teachers. The findings show that most teachers understand the concept of CLT well. However, there are some obstacles that they need to deal with in implementing CLT the classroom. Teachers experience limited access to the target language’s culture, limited time to develop materials for CLT and lack of training in order to improve their teaching skill. Given its importance, more research is still needed to see how this CLT method can be improved in Indonesia teaching context in the future.